Effectiveness of Different Cleaning Solutions in Removing Residual Caries‐Detector Dyes. Issue 3 (1st November 2018) - Tunc, Emine Sen; Sahin, Zeynep; Guler, Eda; Bayrak, Sule; Tuloglu, Nuray
Abstract: Objective: Caries‐detector dyes (CDDs) have proven useful in the identification and removal of carious dentin. However, residues of these cleaning agents may remain in the oral cavity. This study conducted spectrophotomectric analyses to evaluate the effectiveness of different cleaning agents in removing residual CDDs from the oral cavity. Material and Method: Ninety freshly extracted human third‐molar teeth were used in the study. Tooth occlusal surfaces were ground to expose dentin. Specimens were randomly distributed into 3 groups according to CDD [Seek Caries Indicator (SCI), Caries Detector (CD), Caries Marker (CM)], and each group was further divided into 3 sub‐groups according to cleaning solution [distilled water (DW), 3% NaOCl, and 3% H2 O2 )]. CDDs were applied to dentin surfaces according to the manufacturer's instructions and then rinsed with a cleansing solution. The effectiveness of cleaning solutions in removing CDD residues was determined according to color change by comparing spectrophotometric measurements of tooth color before CDD application and after cleaning. Data were analyzed using two‐way analysis of variance (ANOVA) and Tukey's HSD test (α = 0.05). Result: For all CDDs groups, the smallest color differences were observed in the 3% NaOCl sub‐groups ( P  < .05), and the largest in the distilled water sub‐groups ( P  > .05). When compared to the other CDD groups, the SCI group yielded the greatest color differences for all cleaning‐agent sub‐groups. Conclusion: Cleaning solutions such as 3% NaOCl or 3% H2 O2 can be used to remove residual CDD from dentin surfaces. Clinical Significance: This study compared the effectiveness of three different cleaning agents in caries removal process.